2018
DOI: 10.20944/preprints201809.0153.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Exosomes Ameliorated Diabetic Nephropathy by Autophagy Induction through mTOR Signaling Pathway

Abstract: Background: diabetic nephropathy (DN) is a serious complication of diabetes mellitus and a common cause for end stage renal disease. Autophagy has a defensive role against kidney damage caused by hyperglycemia. The mesenchymal stem cells (MSCs) derived exosomes are currently considered as a new promising therapy in chronic renal injury. However, the renal protective mechanism of exosomes on DN has not been completely understood. We examined the potential role of MSCs derived exosomes in enhancement of autophag… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 27 publications
0
30
0
Order By: Relevance
“…Autophagy has also been recently considered as a mechanism to delay DN. Ebrahim et al confirmed that MSC-Exos enhance autophagy and then slow the progression of DN via the mTOR signalling pathway [88]. Jin et al further showed that the ADMSC-Exo can inhibit the Smad1/ mTOR signalling pathway by miRNA-486, which promotes autophagy and inhibits apoptosis in podocytes, thus ameliorating the symptoms of DN [89].…”
Section: Msc-evs and Dnmentioning
confidence: 99%
“…Autophagy has also been recently considered as a mechanism to delay DN. Ebrahim et al confirmed that MSC-Exos enhance autophagy and then slow the progression of DN via the mTOR signalling pathway [88]. Jin et al further showed that the ADMSC-Exo can inhibit the Smad1/ mTOR signalling pathway by miRNA-486, which promotes autophagy and inhibits apoptosis in podocytes, thus ameliorating the symptoms of DN [89].…”
Section: Msc-evs and Dnmentioning
confidence: 99%
“…Autophagy induced by EVs also plays a role in cell survival. MSC-derived EVs increase the expression of the autophagy marker LC3 and beclin-1 but decrease the expression of mTOR and fibrotic marker expression in renal tissue, mechanisms that are involved in the improvement renal function and histology of streptozotocin-induced diabetic nephropathy in rats 57. However, the ability of EVs to promote cell survival is not beneficial in cancer because the release of EVs may support tumor cell survival by reducing the chemotherapeutic drug concentration within the tumor cell.…”
Section: Cellular Homeostasis Modulationmentioning
confidence: 99%
“…The molecular mechanism underlying the induction of autophagy in cancer has not been completely described, but so far, more than 30 autophagy-related genes (ATGs) have been identified (Zhang et al, 2017). Upstream of the ATGs, mammalian target of rapamycin (mTOR) kinase has the most potent impact on autophagy (Ebrahim et al, 2018). mTOR complex 1 (mTORC1) promotes protein synthesis, lipid biogenesis, cell growth, and anabolism and inhibits cellular catabolism by preventing autophagy.…”
Section: Introductionmentioning
confidence: 99%